The Small GTPase RHOA Links SLP65 Activation to PTEN Function in Pre B Cells and Is Essential for the Generation and Survival of Normal and Malignant B Cells - Vadakumchery, Anila; Faraidun, Hemin; Ayoubi, Omar El; Outaleb, Issame; Schmid, Vera; Abdelrasoul, Hend; Amendt, Timm; Khadour, Ahmad; Setz, Corinna; Göhring, Katharina; Lodd, Karoline; Hitzing, Christoffer; et al. (Frontiers in Immunology, 2022)
The generation, differentiation, survival and activation of B cells are coordinated by signals emerging from the B cell antigen receptor (BCR) or its precursor, the pre-BCR. The adaptor protein SLP65 (also known as BLNK) is an important signaling factor that controls pre-B cell differentiation by down-regulation of PI3K signaling. Here, we investigated the mechanism by which SLP65 interferes with PI3K signaling. We found that SLP65 induces the activity of the small GTPase RhoA, which activates PTEN, a negative regulator of PI3K signalling, by enabling its translocation to the plasma membrane. The essential role of RhoA is confirmed by the complete block in early B cell development in conditional RhoA-deficient mice. The RhoA-deficient progenitor B cells showed defects in activation of immunoglobulin gene rearrangement and fail to survive both in vitro and in vivo. Reconstituting the RhoA-deficient cells with RhoA or FoxO1, a transcription factor repressed by PI3K signaling and activated by PTEN, completely restores the survival defect. However, the defect in differentiation can only be restored by RhoA suggesting a unique role for RhoA in B cell generation and selection. In full agreement, conditional RhoA-deficient mice develop increased amounts of autoreactive antibodies with age. RhoA function is also required at later stage, as inactivation of RhoA in peripheral B cells or in a transformed mature B cell line resulted in cell loss. Together, these data show that RhoA is the key signaling factor for B cell development and function by providing a crucial SLP65-activated link between BCR signaling and activation of PTEN. Moreover, the identified essential role of RhoA for the survival of transformed B cells offers the opportunity for targeting B cell malignancies by blocking RhoA function.